2014
DOI: 10.1089/ast.2014.1140
|View full text |Cite
|
Sign up to set email alerts
|

The Fuel Cell Model of Abiogenesis: A New Approach to Origin-of-Life Simulations

Abstract: Abstract:In this paper we discuss how prebiotic geo-electrochemical systems can be modeled as a fuel cell and how laboratory simulations of the origin of life in general can benefit from this systems-led approach. As a specific example, we detail the components of what we have termed the "prebiotic fuel cell" (PFC) operating at a putative Hadean hydrothermal vent, and we present preliminary results utilizing electrochemical analysis techniques and proton exchange membrane (PEM) fuel cell components to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 134 publications
4
32
0
Order By: Relevance
“…A perspective in which poorly integrated progenotes were engaged in rampant HGT and then evolved towards a Darwinian bottleneck, that could have entailed distinct events of cellularization, is consistent with the notion of convergent evolution [20]. Assuming that similar, if not identical, processes of far off-equilibrium phenomena involving geochemical gradients in aqueous environments [14,21,22], could have led repeatedly to the emergence of life in comparable, ancient planetary habitats, alien organisms should have experienced a phase of extensive HGT and ensuing (multiple) cellularization too. From this point onwards it becomes exceedingly difficult to reasonably predict what kind of adaptations putative life, for example, on the icy moons of Jupiter and Saturn, Europa and Enceladus, or on a far-away exoplanet, would evolve in the course of their history.…”
Section: Introductionsupporting
confidence: 53%
“…A perspective in which poorly integrated progenotes were engaged in rampant HGT and then evolved towards a Darwinian bottleneck, that could have entailed distinct events of cellularization, is consistent with the notion of convergent evolution [20]. Assuming that similar, if not identical, processes of far off-equilibrium phenomena involving geochemical gradients in aqueous environments [14,21,22], could have led repeatedly to the emergence of life in comparable, ancient planetary habitats, alien organisms should have experienced a phase of extensive HGT and ensuing (multiple) cellularization too. From this point onwards it becomes exceedingly difficult to reasonably predict what kind of adaptations putative life, for example, on the icy moons of Jupiter and Saturn, Europa and Enceladus, or on a far-away exoplanet, would evolve in the course of their history.…”
Section: Introductionsupporting
confidence: 53%
“…Of particular note is the potential to enable assembly of oligomers into membrane-like films capable of sustaining pH gradients (Fig. 5D), a precursor to establishment of basic metabolic processes (33). Finally, we remark that a diverse array of processes beyond prebiotic biochemistry can be catalyzed in hydrothermal microenvironments.…”
Section: Discussionmentioning
confidence: 85%
“…Yamaguchi et al (2014) reported the FeNiS-catalyzed synthesis of CO and methane under simulated alkaline vent conditions, while Herschy et al (2014) obtained CO and formaldehyde. Simulated hydrothermal vents, while so far falling short of spewing forth vitamins, bases, and proteins, do produce compounds that are central to acetogen and methanogen metabolism, and they produce electrochemical gradients (Barge et al 2014), which Mike Russell (Russell and Hall 1997) has been saying all along are essential for early life.…”
Section: Early Microbial Evolutionmentioning
confidence: 99%